Algorithmic regulation / edited by Karen Yeung, Martin Lodge. - Yeung, Karen (Lawyer); Lodge, Martin, 1972- (Oxford University Press, 2019)
This text provides a range of critical essays examining the use of algorithms to regulate various aspects of contemporary life, and the need to regulate these algorithmic systems, drawing from a broad range of disciplinary expertise.